2007
DOI: 10.1007/s11251-007-9032-7
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the teacher’s role and pupils’ ethnicity and prior knowledge on pupils’ performance and motivation to cooperate

Abstract: How can the teacher bring about effective cooperative learning (CL) in multiethnic elementary classrooms? To answer this question we hypothesized that when the teacher stimulates pupils' helping behaviour (experimental group), this increases pupils' performance and CL motivation more than when the teacher lets pupils fend for themselves (control group). Subjects were 166 pupils from 10 schools. The results show that national pupils in the experimental group outperformed pupils in the control group and teams wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Student language proficiency has been found to be strongly related to learning success (Oortwijn, Boekaerts, & Vedder, 2008), to student approaches to learning (Biggs, 1990) and academic achievement (Collier, 1989;Van der Slik, Driessen, & De Bot, 2006). AfL, with its provision of formative feedback, is a linguistic endeavour.…”
Section: Teacher Efficacymentioning
confidence: 99%
“…Student language proficiency has been found to be strongly related to learning success (Oortwijn, Boekaerts, & Vedder, 2008), to student approaches to learning (Biggs, 1990) and academic achievement (Collier, 1989;Van der Slik, Driessen, & De Bot, 2006). AfL, with its provision of formative feedback, is a linguistic endeavour.…”
Section: Teacher Efficacymentioning
confidence: 99%
“…The data for this article originated from a study by Oortwijn et al (2008a) that focused on student background characteristics (i.e., prior mathematical knowledge and motivation for cooperative learning) and teacher stimulation as key factors in the effectiveness of a mathematics curriculum implementing cooperative learning. An informed consent procedure was followed: Parents or caregivers received an information letter that explained the goal, methods, and procedures of the study.…”
Section: Methodsmentioning
confidence: 99%
“…The original study (Oortwijn et al 2008a) took place in 10 multiethnic fifth-grade classes from 10 schools in the Netherlands where a nine-lesson mathematics curriculum was implemented. Based on their prior mathematics performance, 172 students were placed in either of two types of heterogeneous mathematic competence groups each composed of three to four students (high and average competence or average and low competence) before the start of the curriculum.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that the best predictor of language acquisitionand consequently understanding of the content being taught -is when students have opportunities to practise English within meaningful interactions (Gersten, 1999;Haneda, 2008;Lee, 2004;Mickan, 2007). Strategies that allow ESL students to practise English include informal opportunities for meaningful discussion within the classroom (Olivo, 2003), collaborative learning (Oortwijn, Boekaerts, & Vedder, 2008), and encouraging students to practise writing for multiple contexts and multiple audiences (McCarthey & García, 2005).…”
Section: Teaching Strategies For Deaf and Esl Studentsmentioning
confidence: 99%